Working Capital Management and Profitability in Property Industry: Evidence from ASEAN Countries - Juita Tiur Napitulu; Moch. Doddy Ariefianto (Dinasti International Journal of Economics, Finance & Accounting, 2024)
We are investigating the role of working capital on the profitability of real estate companies. Working capital is at the core of profitability in the property business model. Existing literature has established a negative relationship between working capital and profitability. To verify this hypothesis, we propose a linear regression model that links measures of profitability (ROE and Profit Margin) with measures of working capital (Current Asset to Current Liability Ratio and Working Capital Days); Liquidity (Current Asset to Current Liability Ratio), Leverage (Debt to Total Asset Ratio), Size, and company dummies serving as control variables. The regression model is estimated using a panel data set consisting of 376 companies in the ASEAN region from 2013 to 2022 (3760 annual observations per company). Model selection procedures suggest the application of Feasible Generalized Least Squares (FGLS) due to unobserved heterogeneity and the presence of serial correlation and heteroskedasticity. As expected, we find that working capital has a significant negative relationship with profitability. Subsequent robustness tests indicate consistent findings across specifications and country samples.